Population Pharmacokinetics and Bayesian Estimation of Mycophenolic Acid Exposure in Chinese Renal Allograft Recipients After Administration of EC‐MPS. (10th December 2018) - Chen, Bing; Shao, Kun; An, Hui‐Min; Shi, Hao‐Qiang; Lu, Jia‐Qian; Zhai, Xiao‐Hui; Liu, Xiao‐Xue; Wang, Xiang‐Hui; Xu, Da; Zhou, Pei‐Jun
Abstract: The aim of the present study is to establish a population pharmacokinetic (PPK) model of mycophenolic acid (MPA) and limited sampling strategy models for the estimation of MPA exposure in Chinese adult renal allograft recipients following oral administration of enteric coated mycophenolate sodium (EC‐MPS). A total of 74 sets of full pharmacokinetic profiles and 47 sets of MPA‐sparing samples were collected from 102 renal transplant recipients who received oral EC‐MPS. The MPA concentration was determined by an enzyme‐multiplied immunoassay technique, and the pathophysiologic data were recorded. The PPK model was constructed using nonlinear mixed‐effects modeling, and the limited sampling strategy models for MPA were established by using multiple regression analysis and the maximum a posteriori Bayesian assay based on 2 to 4 sampling time points following EC‐MPS administration. The pharmacokinetics of MPA were best described by a 2‐compartment model with a first‐order absorption process and a lag time of absorption. The clearance of MPA was 12.3 ± 1.14 L/h. Comedicating with cyclosporine A was found to have a significant impact on the clearance/bioavailability of MPA ( P < .01). Sampling strategies consisted of plasma concentration at 1.5, 2, 4 (C1.5‐C2‐C4) hours and 1.5, 2, 4, 6 (C1.5‐C2‐C4‐C6) hours after EC‐MPS administration were shown to be suitable for the estimation of the MPA area under the concentration‐time curve in these patients. The PPK model was acceptable and can describe the pharmacokinetics of MPA in Chinese renal transplant recipients administered EC‐MPS. The area under the concentration‐time curve of MPA in Chinese renal transplant recipients could be estimated through a limited sampling strategy method, based on which individualized immunosuppressive regimens could be designed.